2015
DOI: 10.1080/15980316.2015.1062809
|View full text |Cite
|
Sign up to set email alerts
|

A monodomain-like liquid-crystalline simple cubic blue phase II

Abstract: In this work, a systematic approach to controlling the orientation of a liquid-crystalline simple cubic blue phase (BPII) was carried out using a conventional surface rubbing treatment method. A more uniform lattice plane alignment in BPII was produced than in the liquid-crystalline-body-centered blue phase (BPI) using rubbed polyimide (PI) films on glass substrates. A single-color monodomain-like BPII was achieved regardless of the rubbed PI substrate pretilt angle. Additionally, singlecolor monodomain-like B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 20 publications
(24 reference statements)
2
18
0
Order By: Relevance
“…Doping nematic LCs with chiral dopants induces a cholesteric (Ch) phase. 5 In contrast, the doping of Ch LC with achiral molecules elongates the helical pitch of the Ch phase because the blending of achiral molecules dilutes the chirality of the system. 6 …”
Section: Introductionmentioning
confidence: 99%
“…Doping nematic LCs with chiral dopants induces a cholesteric (Ch) phase. 5 In contrast, the doping of Ch LC with achiral molecules elongates the helical pitch of the Ch phase because the blending of achiral molecules dilutes the chirality of the system. 6 …”
Section: Introductionmentioning
confidence: 99%
“…To confirm the characteristics of cubic BPs, selective reflection for some of these BP blending mixtures was investigated (Figures – ). Figure a,b exhibits that only a single reflection band around 450 nm can be observed in the higher-temperature range in the blending mixture consisting of OH-TII 7 + 40% S811 similar to that for OH-TI 7 , indicating that BPII exists in the high-temperature range of the BP. In addition, another reflection band appears around 500 nm on lowering the temperature down to 45 °C and exhibits an obvious red shift from 497 to 586 nm during the cooling process (Figure b), implying the characteristics of BPI that is caused by the multilattice plane orientations of the different platelet domains, showing two broader and lower peaks in the lower-temperature range of the BP . In comparison, a sharper and higher reflectance peak can be observed in the higher-temperature range of the BP due to relatively uniform alignment.…”
Section: Results and Discussionmentioning
confidence: 91%
“…48−50 In addition, another reflection band appears around 500 nm on lowering the temperature down to 45 °C and exhibits an obvious red shift from 497 to 586 nm during the cooling process (Figure 11b), implying the characteristics of BPI that is caused by the multilattice plane orientations of the different platelet domains, showing two broader and lower peaks in the lower-temperature range of the BP. 50 In comparison, a sharper and higher reflectance peak can be observed in the higher-temperature range of the BP due to relatively uniform alignment. In addition, Figure 11b illustrates that the temperature range of BPII is wider than that of BPI.…”
Section: Phase Transition Behaviors and X-ray Powdermentioning
confidence: 97%
“…For example, Nayek et al fabricated a monodomain BP using an antiparallel rubbed cell, which showed a reduced operating voltage by 27% and hysteresis by 63% due to the enhanced Kerr constant [40]. Similarly, a well-aligned BP II was obtained by cooling from an isotropic state in a rubbed cell, providing significantly improved reflectivity with a narrow photonic band gap [41]. A polarization-independent phase modulator was also developed using monodomain PSBPs [42].…”
Section: Use Of the Alignment Layermentioning
confidence: 99%